ANALISIS YURIDIS AJARAN TURUT SERTA DALAM KASUS ABORTUS PROVOCATUS DENGAN ALASAN KEGAGALAN ALAT KONTRASEPSI - Yonna B. Salamor (Faculty of Law, Universitas Pattimura, 2014)
Abortus provocatus is a controversial case until now because there are pros and cons in the community.In criminal law of Indonesia abortion is a crime provocatus.Perpetrators in the case of abortion provocatus by reason of the failure of contraception is Pregnancy (dader) who want abortion occurs in an abortion, pregnant women can not do the criminal act itself but because of the people assisted by the helper perpetrators will also be punished.